Can the causal mechanisms underlying chronic, serious, and violent offending trajectories be elucidated using the psychopathy construct?. Issue 4 (July 2015) - Corrado, Raymond R.; DeLisi, Matt; Hart, Stephen D.; McCuish, Evan C.
Highlights Problems with criminology's incorporation of the psychopathy construct are discussed. The CAPP model of psychopathy is introduced. Causal mechanisms underlying offending trajectories are proposed.